Lógicas de apropiación del lugar en la arquitectura latinoamericana encrucijada siglos xx-xxi (2008)
The report “Logical of appropriation of the place in the Latin American Architecture, Crossroad XX centuries-XXI” was addressed at the XI Seminar of Latin American architecture that took place in Oaxtepec, Morelos, Mexico (2005). The conference was in charge of Roger Ruiz, María Lanos, Hernán Aldana and Germán Rodríguez, as the result of the Seminar of Latin American Architecture. This text investigates on the aesthetic dimension that addresses the current state of the Latin American architecture. Starting from a meticulous observation of the most outstanding works in the present time, it is given sample of the new contents and sensibilities that have formed inside the formal processes with which this architecture has appropriated the “natural landscape affected by the time like the man’s scenario, the culture and the history” (Niño Murcia, 2000). When trying to refer this processes it shows a group of images and forms of seeing the world, characteristic of the chore architectural Latin American, which attended their realizations mediated by the wide margin of possibilities that offer high technologies.